2002
DOI: 10.1086/341608
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Isolates in East Asia: A Study of Linkage Disequilibrium in the X Chromosome

Abstract: The background linkage disequilibrium (LD) in genetic isolates is of great interest in human genetics. Although many empirical studies have evaluated the background LD in European isolates, such as the Finnish and Sardinians, few data from other regions, such as Asia, have been reported. To evaluate the extent of background LD in East Asian genetic isolates, we analyzed the X chromosome in the Japanese population and in four Mongolian populations (Khalkh, Khoton, Uriankhai, and Zakhchin), the demographic histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 21 publications
4
38
1
Order By: Relevance
“…There is little possibility of genotyping error only in the male suicide completers because the genotype distributions in other groups (male/female controls and female suicide completers) are in Hardy-Weinberg equilibrium. There is also little possibility of false-positive results due to population stratification in our study because the Japanese population is considered ethnically homogeneous due to its geographical and historical isolation (Katoh et al, 2002).…”
Section: Resultsmentioning
confidence: 96%
“…There is little possibility of genotyping error only in the male suicide completers because the genotype distributions in other groups (male/female controls and female suicide completers) are in Hardy-Weinberg equilibrium. There is also little possibility of false-positive results due to population stratification in our study because the Japanese population is considered ethnically homogeneous due to its geographical and historical isolation (Katoh et al, 2002).…”
Section: Resultsmentioning
confidence: 96%
“…By contrast, the Khoton showed affinities with CAS populations based on both mtDNA and Y-chromosome data (Katoh et al 2005a,b;Pipes, Labuda, and Schurr 2008) and may have arisen from a population of Turkic origin that recently migrated into the present territory of Mongolia (Batsuuri 1977;Nyambuu 1992). Interestingly, an earlier analysis of X-chromosome variation in Mongolian groups revealed strong similarities between the Uriankhai and Zakhchin populations (Katoh et al 2002). These data, in the context of historical and ethnographic evidence (Nyambuu 1992), point to genetic admixture as the source of this close genetic relationship.…”
Section: Genetic Diversity Of Mongolian Ethnic Groupsmentioning
confidence: 84%
“…These studies showed a higher degree of polymorphism in the distribution of HLA haplotypes among Koreans than in Japanese. Recently, it has been reported that the Japanese people have a relatively higher level of BLD than the Finnish, European American, and Sardinian populations, although the results were restricted to the X chromosome and mitochondirial DNA (Katoh et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Although many empirical studies have evaluated the BLD in European isolates, such as the Finnish and Sardinians (de la Chapelle et al, 1998;Eaves et al, 2000;Angius et al, 2001), few data from other region, such as Asia, have been reported (Katoh et al, 2002).…”
Section: Introductionmentioning
confidence: 99%